PENERAPAN METODE PERMAINAN SIMULASI PADA MATERI KEARSIPAN UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR SISWA - Nur Amaliyah, ; Ainul Yaqin, (Pendidikan Ekonomi, 2012)
The problems of this study are: (1) how does the teacher conducts the simulation  game, (2) How is the students activities during the learning process, (3) How can the simulation game enhance the learning result (4) How can the simulation game enhance the students motivation, (5) How do the students response this simulation game. This study applies the Class Action Research while the data collected trough questionnaire, test and documentation. This research is done in two cycles. The subject of this study is the XI APK class students of SMK Muhammadiyah 2 Gresik. The result of this study shows the students learning motivation increased after applying the simulation game method. It is proved by the students motivation questionnaire, before this method applied the students motivation is 49,5% and after applying this method, the students motivation become 78%. The students average point is also increased in each cycle, the first pre- test is 70,37%, the second pre-test is 92,59%, whilst the first post-test is 77,78% and the second posttestis 96,29%. Furthermore, the questionnaire shows that students agreed with the implementation of this method in the archives lesson.